Analysis of dead on arrival at emergency department of Patan Hospital - Bajracharya, Sumana; Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Introduction: Prehospital care plays an important role in reducing the death on arrival from injuries and critical illnesses. This study is aimed to analyze the prevalence of the patients who were brought dead on arrival at emergency department of Patan hospital. Method: This is a cross sectional study conducted by reviewing the record of patient who were brought dead to emergency department. The records from 15th June 2017 to 15th May 2018 were analyzed. Result: Total 48,853 patient visited Patan Hospital emergency department in one year. Out of these patients 98 (20 out of 10,000 patients) had mortality in emergency department while 241 (49 out of 10,000) were dead on arrival to emergency department. Conclusion: Twice the number of patients are dying on the road compare to inside emergency department.